Jahān-i dānish - Masʿūdī, Sharaf al-Dīn-i, (Miras Maktoob, ISBN: 9789004365452., 2019)
Sharaf al-Din Mas'ūdi (6th/12th cent.) was a philosopher, astronomer, mathematician and logician. A native of Marw, he spent a large part of his life in Bukhara and Samarqand, Transoxiana. In Bukhara he had a number of debates with the philosopher and theologian Fakhr al-Dīn Rāzī (d. 606/1210), described in the latter's Munāẓarāt jarat fī bilād Mā warāʾ al-nahr . From among his philosophical works, his critical notes to Avicenna's (d. 428/1037) al-Ishārāt wal-tanbīhāt deserve special mention. In the sciences, he wrote a work on astronomy and geography called al-Kifāya fī ʿilm al-hayʾa . In the introduction to this work he explains that he composed it at the request of a friend and that it is based on the works of others, among then Ibn al-Haytham (d. ca. 432/1040-41) and Kushyār b. Labbān (fl. late 4th/10th cent.). Afterwards, he translated it into Persian-this time without mentioning his sources-calling it Jahāni- dānish , published in this volume.